1999
DOI: 10.1038/sj.bjc.6690246
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the PTEN/MMAC1 gene in archival low grade and high grade gliomas

Abstract: SummaryThe PTEN gene, located on 10q23.3, has recently been described as a candidate tumour suppressor gene that may be important in the development of advanced cancers, including gliomas. We have investigated mutation in the PTEN gene by direct sequence analysis of PCR products amplified from samples microdissected from 19 low grade (WHO Grade I and II) and 27 high grade (WHO grade III and IV) archival, formalin-fixed, paraffin-embedded gliomas. Eleven genetic variants in ten tumours have been identified. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
(27 reference statements)
1
30
2
2
Order By: Relevance
“…These findings contrast with those in breast cancer, where 10q23 LOH has been associated with adverse prognostic factors, including higher stage, higher tumour grade, and loss of oestrogen receptors Garcia et al, 1999). In gliomas, the presence of PTEN mutations correlated with high tumour grade (Rasheed et al, 1997;Duerr et al, 1998;Davies et al, 1999;Zhou et al, 1999). However, among high-grade glioblastomas, in which the incidence of PTEN mutation is highest, PTEN mutations do not appear to influence overall survival (Zhou et al, 1999).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…These findings contrast with those in breast cancer, where 10q23 LOH has been associated with adverse prognostic factors, including higher stage, higher tumour grade, and loss of oestrogen receptors Garcia et al, 1999). In gliomas, the presence of PTEN mutations correlated with high tumour grade (Rasheed et al, 1997;Duerr et al, 1998;Davies et al, 1999;Zhou et al, 1999). However, among high-grade glioblastomas, in which the incidence of PTEN mutation is highest, PTEN mutations do not appear to influence overall survival (Zhou et al, 1999).…”
Section: Discussioncontrasting
confidence: 48%
“…Somatic mutations of PTEN have been found in sporadic tumours of the breast Chen et al, 1999;Freihoff et al, 1999), thyroid , head and neck Shao et al, 1998), central nervous system (Liu et al, 1997;Rasheed et al, 1997;Teng et al, 1997;Wang et al, 1997;Bostrom et al, 1998;Chiariello et al, 1998;Duerr et al, 1998;Maier et al, 1998;Davies et al, 1999;Zhou et al, 1999), endometrium (Kong et al, 1997;Risinger et al, 1997;Tashiro et al, 1997;Simpkins et al, 1998;Mutter et al, 2000;Yaginuma et al, 2000), ovary (Tashiro et al, 1997;Teng et al, 1997;Obata et al, 1998;Saito et al, 2000), prostate Dong et al, 1998;Gray et al, 1998;Pesche et al, 1998;Suzuki et al, 1998;Feilotter et al, 1999), kidney Alimov et al, 1999), lung (Kohno et al, 1998;Yokomizo et al, 1998), and in melanomas Tsao et al, 1998) and non-Hodgkins lymphomas (Gronbaek et al, 1998;Nakahara et al, 1998;Sakai et al, 1998;Butler et al, 1999;Dahia et al, 1999). Whether loss of PTEN function plays a role in the development of Barrett's oesophagusassociated adenocarcinoma (BOAd) is not known.…”
mentioning
confidence: 99%
“…25,26 PTEN was mutated or deleted homozygously in glioma, endometrial, and breast carcinoma tumors. [27][28][29] It was reported that PTEN mutations were identified in small cell carcinomas, but not in non-small-cell carcinomas. 30,31 We found that the frequency of the loss of expression of PTEN was higher in high-grade neuroendocrine carcinoma than in classic large cell carcinoma or carcinoid tumor, and the differences were significant; however, the difference was not significant between large cell neuroendocrine carcinoma and small cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials with tumstatin, therefore, might benefit from stratification of patients based on PTEN status. This type of stratification could easily be done in glioblastoma multiforme, only 30% of which exhibit PTEN alterations (45)(46)(47). Alternatively, the present work suggests that inhibition of the Akt/mTOR axis by agents, such as epidermal growth factor receptor inhibitors or rapamycin, might further sensitize tumors to the direct antitumor actions of T3.…”
Section: Discussionmentioning
confidence: 99%